People with schizophrenia and depression have a low omega-3 index. (July 2016) - Parletta, Natalie; Zarnowiecki, Dorota; Cho, Jihyun; Wilson, Amy; Procter, Nicholas; Gordon, Andrea; Bogomolova, Svetlana; O'Dea, Kerin; Strachan, John; Ballestrin, Matt; Champion, Andrew; Meyer, Barbara J
Abstract: Cardiovascular disease (CVD) is higher in people with mental illness and is associated with a 30 year higher mortality rate in this population. Erythrocyte docosahexaenoic acid (DHA) plus eicosapentaenoic acid (EPA) (omega-3 index)≤4% is a marker for increased mortality risk from CVD while >8% is protective. Omega-3 polyunsaturated fatty acids are also important for brain function and may ameliorate symptoms of mental illness. We investigated the erythrocyte omega-3 index in people with mental illness. One hundred and thirty adults aged 18–65 years (32.6% male) with schizophrenia (n=14) and depression (n=116) provided blood samples and completed physiological assessments and questionnaires. Both populations had risk factors for metabolic syndrome and CVD. The average omega-3 index was 3.95% (SD=1.06), compared to an estimated 5% in the Australian population. These data indicate an unfavourable omega-3 profile in people with mental illness that could contribute to higher CVD risk. Highlights: People with mental illness have higher mortality, largely due to heart disease. An omega-3 index (EPA + DHA) <4% confers high risk for mortality from heart disease. An omega-3 index >8% confers highest protection from heart disease. This sample of people with mental illness had an omega-3 index of 3.95%. Further research of the omega-3 index in people with mental illness is warranted.